PERAN GURU BIMBINGAN DAN KONSELING DALAM MENINGKATKAN MANAJEMEN WAKTU SISWA UNTUK MENGURANGI KEBIASAAN TERLAMBAT MASUK SEKOLAH [THE ROLE OF GUIDANCE AND COUNSELING TEACHERS IN IMPROVING STUDENT TIME MANAGEMENT TO REDUCE THE HABIT OF BEING LATE TO SCHOOL] - Tea, Maria Giuseppina Ee; Bone, Matilda Pia (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This study aims to analyze the role of Guidance and Counseling (BK) teachers in improving students' time management skills to reduce the habit of being late to school. The phenomenon of student tardiness is still a serious problem in various schools and is often associated with weak discipline and time management skills. This study uses a qualitative approach with a case study type conducted at SMA Negeri 4 Kupang from August to September 2025. Research participants consisted of BK teachers, homeroom teachers, and grade XI students selected through purposive sampling techniques. Data were collected through semi-structured interviews, participant observation, and documentation studies, then analyzed using data reduction, data presentation, as well as drawing conclusions and verification. The results of the study revealed three main themes, namely: (1) the role of BK teachers as facilitators of student self-awareness in understanding and improving time management habits, (2) the application of disciplinary development strategies based on reflective and empathetic counseling, and (3) collaboration between BK teachers, homeroom teachers, and parents in establishing positive routines and supporting students' time discipline.